2020
DOI: 10.1111/gcb.15442
|View full text |Cite
|
Sign up to set email alerts
|

Two centuries for an almost complete community turnover from native to non‐native species in a riverine ecosystem

Abstract: Non‐native species introductions affect freshwater communities by changing community compositions, functional roles, trait occurrences and ecological niche spaces. Reconstructing such changes over long periods is difficult due to limited data availability. We collected information spanning 215 years on fish and selected macroinvertebrate groups (Mollusca and Crustacea) in the inner‐Florentine stretch of the Arno River (Italy) and associated water grid, to investigate temporal changes. We identified an almost c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 188 publications
(151 reference statements)
2
67
0
Order By: Relevance
“…Despite an increasing number of indicators and alarming reports on the rapid decline of biodiversity globally (Díaz et al 2020;Haubrock et al 2021b), efforts to halt biodiversity losses have remained insufficient (Hulme 2009;Scalera 2010;Rayment et al 2018). Notwithstanding the multiple signals of the rapid decline of natural capital worldwide, global economic resources allocated to prevent and mitigate such losses have not proven adequate to meet conservation management goals, or have been designated inefficiently (Murdoch et al 2007;Underwood et al 2008;Stokstad 2010;McCarthy et al 2012;Waldron et al 2013Waldron et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasing number of indicators and alarming reports on the rapid decline of biodiversity globally (Díaz et al 2020;Haubrock et al 2021b), efforts to halt biodiversity losses have remained insufficient (Hulme 2009;Scalera 2010;Rayment et al 2018). Notwithstanding the multiple signals of the rapid decline of natural capital worldwide, global economic resources allocated to prevent and mitigate such losses have not proven adequate to meet conservation management goals, or have been designated inefficiently (Murdoch et al 2007;Underwood et al 2008;Stokstad 2010;McCarthy et al 2012;Waldron et al 2013Waldron et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Haubrock et al (2019) argued that the strong resource overlap with the co-occurring invasive species I. punctatus could be the reason the less competitive S. glanis juveniles shifted to other potential food sources. However, invasive, and potentially predatory species like Dikerogammarus villosus, Palaemon sp., or P. parva (the latter combined with A. alburnus as cyprinids) are highly abundant in the section of the Arno studied (Haubrock et al 2021a). Accordingly, we found that cyprinids comprised a considerable portion of the S. glanis diet.…”
Section: Discussionmentioning
confidence: 47%
“…While it is difficult to determine the reason for this, it was previously argued that major drivers could be either competition with I. punctatus or increasingly unsuitable environmental conditions (Haubrock et al 2020). While the Arno River is not the ideal environment to investigate this predator's impact on nearly absent native species (Haubrock et al 2021a), the present study indicated this species has a generalist diet that could impact multiple resource types. Based on the prey occurrences observed, it can also be argued that the diet of S. glanis, and therefore its feeding impact on the community of potential prey, can affect species beyond those previously identified as prey species such as cyprinids and crustaceans.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This is particularly true in freshwater ecosystems, which are vulnerable to biological invasions owing to the strong link of humans to water, the inconspicuousness of aquatic ecosystems (Rico‐Sánchez et al, 2020), and the high interconnectedness, and thus the dispersal ability, of freshwater species compared with terrestrial species (Selge, Fischer & van der Wal, 2011; Tricarico, Junqueira & Dudgeon, 2016). As a result, freshwater communities are often dominated by multiple invasive alien species (IAS) living in sympatry and interacting with each other (Gamradt & Kats, 1996; Kiesecker & Blaustein, 1998; Haubrock et al, 2020), and some of these may have facilitative effects (Crane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%